Strawberry Extract as a Tooth Stain Remover - Ita Yulita; Ita Astit Karmawati; Rahaju Budiarti (Humanistic Network for Science and Technology (HNST), 2019)
This study aimed to compare the effectiveness of strawberry extract with100%, 75%, 50% and 25% concentration in cleaning the extrinsic stain on the teeth. The sample of the study was 32 permanent anterior teeth that were already extracted, consisting of each 16 maxillary and mandibular anterior teeth and all samples have an extrinsic stain. The samples were randomly divided into 4 groups, each group consisting of 8 teeth was treated by applying the strawberry extract with the concentrations of 100%, 75%, 50% and 25%. After 5 minutes, the teeth were rinsed and dried. The study was conducted in vitro for five consecutive days with twice treatment daily. Intensity Score and Extension Score of the stain were measured using the Lobene Stain Index. All samples experienced a decrease in both the Intensity and Extension Scores, the largest decrease in Intensity and Extension Score were obtained from strawberry extracts with concentration of 100%. The significant decrease in the Intensity Score occurs on the third day and continues until the fourth and fifth days, while the significant decrease in the Extention Score occurs on the fourth day and continues until the fifth day. The four group of the strawberry extract concentrations gave a decrease in the score, which distinguishes the treatment frequency. The higher the concentration, the frequency would be less in lowering stain score, whereas at low concentration the decrease of score require more frequency. Keywords: Extrinsic stain, Strawberry extract